The Impact of Varying Food Availability on Gene Expression in the Liver: Testing the Match-Mismatch Hypothesis - Feige-Diller, Janina; Herrera-Rivero, Marisol; Witten, Anika; Stoll, Monika; Kaiser, Sylvia; Richter, S. Helene; Sachser, Norbert (Frontiers in Nutrition, 2022)
Background: During early phases of life, such as prenatal or early postnatal development and adolescence, an organism’s phenotype can be shaped by the environmental conditions it experiences. According to the Match-Mismatch hypothesis (MMH), changes to this environment during later life stages can result in a mismatch between the individual’s adaptations and the prevailing environmental conditions. Thus, negative consequences in welfare and health can occur. We aimed to test the MMH in the context of food availability, assuming adolescence as a sensitive period of adaptation. Methods: We have previously reported a study of the physiological and behavioral effects of match and mismatch conditions of high (ad libitum) and low (90% of ad libitum intake) food availability from adolescence to early adulthood in female C57BL/6J mice (n=62). Here, we performed RNA-sequencing of the livers of a subset of these animals (n=16) to test the effects of match and mismatch feeding conditions on the liver transcriptome. Results: In general, we found no effect of the match-mismatch situations. Contrarily, the amount of food available during early adulthood (low vs high) drove the differences we observed in final body weight and gene expression in the liver, regardless of the amount of food available to the animals during adolescence. Many of the differentially expressed genes and the corresponding biological processes found to be overrepresented overlapped, implicating common changes in various domains. These included metabolism, homeostasis, cellular responses to diverse stimuli, transport of bile acids and other molecules, cell differentiation, major urinary proteins, and immunity and inflammation. Conclusions: Our previous and present observations found no support for the MMH in the context of low vs high food availability from adolescence to early adulthood in female C57BL/6J mice. However, even small differences of approximately 10% in food availability during early adulthood resulted in physiological and molecular changes with potential beneficial implications for metabolic diseases.